A new species of Velvet Gecko (Oedura: Diplodactylidae) from the limestone ranges of the southern Kimberley, Western Australia - Oliver, Paul M.; Laver, Rebecca J.; Melville, Jane; Doughty, Paul (Zootaxa, 2014)
We describe a new species of large Oedura from the Oscar Range on the southern edge of the Kimberley Craton in north-western Australia. Oedura murrumanu sp. nov. can be distinguished from all congeners by the combination of large size (snout-vent length to 103 mm), moderately long and slightly swollen tail, tiny scales on the dorsum, fringe of laterally expanded lamellae on each digit, and 6–7 paired distal subdigital lamellae on the fourth toe. The new species is the first endemic vertebrate known from the limestone ranges of the southern Kimberley; however, this area remains poorly surveyed and further research (particularly wet season surveys and genetic analyses) is required to better characterise regional biodiversity values.